Changes in Tea Plant Secondary Metabolite Profiles as a Function of Leafhopper Density and Damage - Scott, Eric R.; Li, Xin; Wei, Ji-Peng; Kfoury, Nicole; Morimoto, Joshua; Guo, Ming-Ming; Agyei, Amma; Robbat, Albert; Ahmed, Selena; Cash, Sean B.; Griffin, Timothy S.; Stepp, John R.; et al. (Frontiers in Plant Science, 2020)
Insect herbivores have dramatic effects on the chemical composition of plants. Many of these induced metabolites contribute to the quality (e.g. flavor, human health benefits) of specialty crops such as the tea plant (Camellia sinensis). Induced chemical changes are often studied by comparing plants damaged and undamaged by herbivores. However, when herbivory is quantitative, the relationship between herbivore pressure and induction can be linearly or non-linearly density dependent or density independent, and induction may only occur after some threshold of herbivory. The shape of this relationship can vary among metabolites within plants. The tea green leafhopper (Empoasca onukii) can be a widespread pest on tea, but some tea farmers take advantage of leafhopper-induced metabolites in order to produce high-quality “bug-bitten” teas such as Eastern Beauty Oolong. To understand the effects of increasing leafhopper density on tea metabolites important for quality, we conducted a manipulative experiment exposing tea plants to feeding by a range of E. onukii densities. After E. onukii feeding, we measured volatile and non-volatile metabolites, and quantified percent damaged leaf area from scanned leaf images. E. onukii density had a highly significant effect on volatile production, while the effect of leaf damage was only marginally significant. The volatiles most responsive to leafhopper density were mainly terpenes that increased in concentration monotonically with density, while the volatiles most responsive to leaf damage were primarily fatty acid derivatives and volatile phenylpropanoids/benzenoids. In contrast, damage (percent leaf area damaged), but not leafhopper density, significantly reduced total polyphenols, epigallocatechin gallate (EGCG), and theobromine concentrations in a dose-dependent manner. The shape of induced responses varied among metabolites with some changing linearly with herbivore pressure and some responding only after a threshold in herbivore pressure with a threshold around 0.6 insects/leaf being common. This study illustrates the importance of measuring a diversity of metabolites over a range of herbivory to fully understand the effects of herbivores on induced metabolites. Our study also shows that any increases in leafhopper density associated with climate warming, could have dramatic effects on secondary metabolites and tea quality.